Preparing Students for Globalization Without Traveling: A Multi-Layered Intercultural Technology-Mediated American and Israeli Collaboration - Haughton, Noela A.; Schödl, Michal M. (Frontiers in Education, 2020)
Costly exchange programs are not the only way to achieve global competence. This paper describes a model for the use of collaborative and cost-effective course assignment to develop global competence among student. We used this model to develop and implement a technology-mediated local-global experience between two undergraduate programs: American Teacher Education and Israeli Hotel, Food and Tourism Management. The 2-year collaboration was built on a three-layer pedagogical model: Layer 1 (instructor collaboration), Layer 2 (joint task), and Layer 3 (student collaboration). Three hypotheses were tested with pre- and post-project survey data: increased assessment and global competencies self-efficacy for American students; and, increased global competencies self-efficacy for Israeli students. Year 1 results supported the hypothesis for Israeli students but failed to support both hypotheses for American students. Subsequent refinements to the three collaboration layers were made. Year 2 results supported all three hypotheses, establishing the potential value of this pedagogical model to implement effective technology-mediated local-global international experiences. Limitations and further studies are discussed.